CEO Compensation, Change, and Corporate Strategy - DOW, JAMES; RAPOSO, CLARA C. (Journal of Finance, 2005)
ABSTRACT CEO compensation can influence the kinds of strategies that firms adopt. We argue that performance‐related compensation creates an incentive to look for overly ambitious, hard to implement strategies. At a cost, shareholders can curb this tendency by precommitting to a regime of CEO overcompensation in highly changeable environments. Alternatively shareholders can commit to low CEO pay, although this requires a commitment mechanism (either by the board of the individual company, or by the society as a whole) to counter the incentive to renegotiate upwards. We study the conditions under which the different policies for CEO compensation are preferred by shareholders.